Penerapan Metode Pembelajaran Kolaboratif dalam Meningkatkan Hafalan Al-Qur’an Siswa di MA Tahfizhul Qur’an Simbar Tampo Tahun 2024-2025 - Muhamad Nasrulloh; Hadiqoh Asmuni; Mursidah Mursidah (CV. Lentera Literasi Indonesia, 2026)
This study aims to describe the implementation of the collaborative learning method, analyze the forms of cooperation among students, and identify active student interaction in Qur’an memorization activities. This research employs a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews, and documentation, with the main informants consisting of the principal, Qur’an memorization supervisors, and students enrolled in the tahfidz program. Data were analyzed using Miles and Huberman’s interactive model, which involves three stages: data reduction, data presentation, and conclusion drawing. The research findings indicate that: (1) the implementation of the collaborative method is carried out through strategies such as paired murojaah, musyafahah, tasmi’, and group discussions, which effectively enhance memorization consistency; (2) student cooperation is evident in activities such as listening to each other’s recitations, providing motivation, and assisting peers who face memorization difficulties; and (3) active student interaction is reflected in two-way communication, group involvement, and shared responsibility for memorization achievements. Overall, the collaborative learning method has proven to not only improve the quality of students’ memorization but also foster the values of ukhuwah Islamiyah (Islamic brotherhood), independence, and a spirit of mutual assistance in the tahfidz education process.